Performa Adsorpsi Karbon Aktif dari Kulit Kopi untuk Menurunkan Asam Lemak Bebas (FFA) pada Minyak Jelantah - Yunira, Eka Nur'azmi; Putra, Tamam Athallah Rhely; Pratama, Borneo Satria; Witoyo, Jatmiko Eko; Pangestuti, Martasari Beti (Universitas Quality, 2025)
Coffee husk-activated carbon is a promising biomass for use as an adsorbent due to its composition and abundance. This study aimed to analyze the performance of coffee husk-activated carbon in reducing the free fatty acid (FFA) content of used palm cooking oil. The study examined the effects of potassium hydroxide (KOH) concentration, adsorption time, and the mass of activated carbon. The activated carbon was produced through carbonization at a temperature of 300–400, followed by activation using 0 M, 1 M, and 2 M of KOH solutions. The results showed that the reductions in FFA levels at various adsorption times (2, 4, and 6 hours) were 24.219%, 33.828%, and 46.016%, respectively. The longer the adsorption time, the greater the reduction in FFA levels. In mass variations (0.1, 0.3, and 0.5 g) for 100 ml of used palm cooking oil, the reductions in FFA levels for 0 M, 1 M, and 2 M KOH-activated carbon were 40.234%, 47.968%, and 50.781%, respectively. The study found that increasing adsorption time and the mass of coffee husk-activated carbon resulted in lower FFA levels in used palm cooking oil. The highest percentage reduction in FFA levels, 50.781%, was achieved using 2 M KOH-activated carbon with a mass of 0.5 grams using and 6 hours for adsorption time. These findings suggested that coffee husk-activated carbon was a viable and sustainable adsorbent for improving the quality of used palm cooking oil, potentially reducing its environmental impact and enhancing its reuse potential in various applications.